Peculiarities of Applying the Rates of Customs Duties in the Process of Integration of the Republic of Uzbekistan Into the EEU - Miltikbaevich, Suyunov Abdunor; Umidjonkizi, Najmiddinova Marjona (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is devoted to the study of the implementation of the foreign trade policy of the Republic of Uzbekistan related to customs activities. It pays special attention to the possible entry of the Republic of Uzbekistan into the Eurasian Economic Union, and also considers the positive and negative aspects of our country’s accession to this regional economic integration structure